The effectiveness of first-generation antihistamines in the treatment of allergic diseases in children - A.E. Abaturov; E.L. Krivusha; E.A. Agafonova; N.M. Tokarevа; V.L. Babich (Zaslavsky O.Yu., 2018)
The article presents modern information on the clinical application, effectiveness and safety of the first-generation H1-antihistamine - dimetindene maleate. A brief description of the drug is given, the main indicators of its pharmacokinetics and pharmacodynamics are described. The attention is focused on the main pharmacological mechanisms of the clinical effects of the drug. An analysis of the results of clinical studies using dimetindene maleate in allergic and infectious diseases of the skin in children has been carried out. A brief description is given of the drug Phenokit appeared on the pharmaceutical market of Ukraine, the main indications for its administration are substantiated.